2015
DOI: 10.4315/0362-028x.jfp-14-418
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in Stored U.S. Barley and Wheat

Abstract: Ochratoxin A (OTA) is a mycotoxin of significant health concern that is present in a variety of cereal grains and other foods around the world. Although OTA contamination can occur prior to harvest, it is largely considered a storage issue that can be controlled through the implementation of proper storage practices. Barley, durum, and hard red spring wheat samples that had been stored for various lengths of time were collected (n = 262) over a period of 2 years by multiple commercial grain companies located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Study analyzed samples of barley, hard red spring wheat, and durum wheat stored for different durations by several commercial companies involved in grain processing in the northern and northwestern US Great Plains region had OTA in about 12% of samples, and about 81% of the samples were stored for at least 6 months. In Germany, a study analyzed samples of grains between 1991 and 1993, stored for different durations, and reported that about 54% of the samples had OTA, and in 2% levels of OTA were above 3 ng/g [86]. Many studies done in Europe reported higher levels of OTA in organic crops in comparison with conventional beer, oat bran, and wheat samples meant for consumption by humans [87,88].…”
Section: Ochratoxinsmentioning
confidence: 99%
“…Study analyzed samples of barley, hard red spring wheat, and durum wheat stored for different durations by several commercial companies involved in grain processing in the northern and northwestern US Great Plains region had OTA in about 12% of samples, and about 81% of the samples were stored for at least 6 months. In Germany, a study analyzed samples of grains between 1991 and 1993, stored for different durations, and reported that about 54% of the samples had OTA, and in 2% levels of OTA were above 3 ng/g [86]. Many studies done in Europe reported higher levels of OTA in organic crops in comparison with conventional beer, oat bran, and wheat samples meant for consumption by humans [87,88].…”
Section: Ochratoxinsmentioning
confidence: 99%
“…A higher percentage (76%) was obtained in Croatia by Puntaric et al (2001). Also, OTA was detected in 12.2% of stored wheat samples in USA (Kuruc et al 2015). From India, wheat samples were contaminated with detectable quantities of OTA ranging from 1.36 to 21.17 mg/ kg including 13 (26%) samples exceeding the level of 5 mg/kg (Kumar et al 2012).…”
Section: Ota Contamination In Wheat Grainmentioning
confidence: 99%
“…The toxin is found mainly to contaminate cereal grains (wheat, corn, rye, barley) but it can also be found in rice, soybeans, coffee, cacao, beans, peas, peanuts, and dry fruits like figs, raisins, etc. ( Kuruc et al, 2015 ; Palumbo et al, 2015 ). It is also present in beer ( Nguyen and Ryu, 2014 ), wine and grape juice ( Terra et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%